First cases of Zika virus–infected US blood donors outside states with areas of active transmission. Issue 3 (23rd February 2017) - Williamson, Phillip C.; Linnen, Jeffrey M.; Kessler, Debra A.; Shaz, Beth H.; Kamel, Hany; Vassallo, Ralph R.; Winkelman, Valerie; Gao, Kui; Ziermann, Rainer; Menezes, Juscilene; Thomas, Stephen; Holmberg, Jerry A.; et al.
Abstract : BACKGROUND: Zika virus (ZIKV) is transmitted by Aedes mosquitos and can result in severe congenital and adult neurologic abnormalities. ZIKV has rapidly spread northward through Central America and the Caribbean and autochthonous cases have been identified in the continental United States. High rates of ZIKA RNA positivity were detected in blood donors during previous epidemics. ZIKV transmission by transfused blood from healthy donor components has been a growing concern. STUDY DESIGN AND METHODS: Individual‐donation aliquots of plasma from volunteer blood donors were tested individually with an investigational Procleix ZIKV assay. Initially reactive samples were tested for ZIKV RNA in plasma and red blood cells (RBCs) and for ZIKV‐specific antibodies in serum. A confirmed positive classification required confirmation of RNA and/or detection of ZIKV antibodies in index and/or follow‐up samples. RESULTS: Between September 19 and November 30, 2016, a total of 466, 834 donations were screened for ZIKV RNA. Five donors (one in approx. 93, 000) were reactive for ZIKV RNA by both the Procleix ZIKV assay and supplemental testing. The donations were collected outside areas considered as having active transmission, and all five donors had travel exposures. A lookback case demonstrated no infection despite transfusion of a Zika IgG–positive platelet (PLT) component with probable low levels of ZIKV RNA. CONCLUSIONS: This report describes the first ZIKV‐positive donors detected outside areas with active transmission. These donors most likely represent travel‐acquired "tail‐end infections" with prolonged RBC‐associated ZIKV RNA. The lack of transmission to the recipient of an apheresis PLT may suggest that these units are not infectious.